Ultra-broadband carpet cloak for transverse-electric polarization. (1st April 2016) - Deng, Ye; Xu, Su; Zhang, Runren; Zheng, Bin; Chen, Hua; Gao, Fei; Yu, Faxin; Zhang, Baile; Chen, Hongsheng
Abstract: Magnetism is a necessity in constructing macroscopic metamaterial invisibility cloaks that are theoretically designed by transformation optics, but will generally limit the cloaking bandwidth to an impractically narrow range. To meet the broad bandwidth demand, magnetism has been fully abandoned in previous demonstrations of macroscopic carpet cloaking, whose approach, however, cannot apply to a transverse-electric (TE) polarization. To fill this gap, here we experimentally demonstrate an ultra-broadband magnetic carpet cloak for the TE polarization. The cloak is made of non-resonant closed-ring metamaterials with little dispersion and the cloaking performance is confirmed with both time-domain simulation and frequency scanning measurement over a broad bandwidth corresponding to a pulse signal illumination.